Impacts of variable renewable energy on wholesale markets and generating assets in the United States: A review of expectations and evidence. (March 2020) - Mills, Andrew D.; Levin, Todd; Wiser, Ryan; Seel, Joachim; Botterud, Audun
Abstract: We synthesize available literature, data, and analysis on the degree to which growth in variable renewable energy (VRE) has impacted or might in the future impact bulk power system assets, pricing, and costs in the United States. Most studies of future scenarios indicate that VRE reduces wholesale energy prices and capacity factors of thermal generators. Traditional baseload generators are more exposed to these changing market conditions than low-capital cost and more flexible intermediate and peak-load generators. From analysis of historical data we find that VRE is already influencing the bulk power market through changes in temporal and geographic patterns areas with higher levels of VRE. The most significant observed impacts have concentrated in areas with significant VRE and/or nuclear generation along with limited transmission, with negative pricing also often occurring during periods with lower system-wide load. So far, however, VRE, has had a relatively modest impact on historical average annual wholesale prices across entire market regions, at least in comparison to other drivers. The reduction of natural gas prices is the primary contributor to the decline in wholesale prices since 2008. Similarly, VRE impacts on thermal plant retirements have been limited and there is little relationship between the location of recent retirements and VRE penetration levels. Although impacts on wholesale prices have been modest so far, impacts of VRE on the electricity market will be more significant under higher VRE penetrations. Highlights: Synthesize literatureand data on impacts of variable renewable energy on power system assets, pricing, and cost. Contrast impacts from future scenarios with historical observed impacts in the U.S. Wind & solar have had relatively modest impact on historical average annual wholesale prices. Little relationship between the location of recent thermal plant retirements and wind & solar penetration levels. Impacts of wind & solar on the electricity market will be more significant under higher penetrations.